Generalizing across moral sub-domains: infants bidirectionally link fairness and unfairness to helping and hindering - Gill, Inderpreet K.; Sommerville, Jessica A. (Frontiers in Psychology, 2023)
Across two experiments, we investigated whether infants use prior behavior to form expectations about future behavior within the moral domain, focusing on the sub-domains of fairness and help/harm. In Experiment 1, 14-to 27-month-old infants were familiarized to an agent who either helped or hindered another agent to obtain her goal. At test, infants saw the helper or hinderer perform either a fair or unfair distribution of resources to two recipients. Infants familiarized to helping looked longer to the unfair distribution than the fair distribution at test, whereas infants familiarized to hindering looked equally at both test events, suggesting that hindering led infants to suspend baseline expectations of fairness. In Experiment 2, infants saw these events in reverse. Following familiarization to fair behavior, infants looked equally to helping and hindering; in contrast, following familiarization to unfair behavior, infants looked significantly longer to helping than hindering on test, suggesting that prior unfair behavior led infants to expect the agent to hinder another agent's goals. These results suggest that infants utilize prior information from one moral sub-domain to form expectations of how an individual will behave in another sub-domain, and that this tendency seems to manifest more strongly when infants initially see hindering and unfair distributions than when they see helping and fair distributions. Together, these findings provide evidence for consilience within the moral domain, starting by at least the second year of life.